Surgical Instrument’s Tip Fracture During Cataract Surgery - Azlina Mokhtar; Zalifa Zakiah Asnir; Maimunah Abdul Muna'aim; Umi Kalthum Md Noh (USIM Press, 2024)
Vol. 7 No. 3 (2021): Special Issue on Clinical Scenarios In Medicine, A Malaysian Experience (Case Report)